2013
DOI: 10.3349/ymj.2013.54.3.690
|View full text |Cite
|
Sign up to set email alerts
|

The Studer Orthotopic Neobladder: Long-Term (More Than 10 Years) Functional Outcomes, Urodynamic Features, and Complications

Abstract: PurposeRadical cystectomy and urinary diversion are the standard treatment for invasive bladder cancer. We analyzed the long-term (>10 years postoperatively) functional outcomes, complications, and urodynamic findings in a single center series of patients who underwent cystectomy and a Studer ileal neobladder substitution.Materials and MethodsA retrospective chart review of 108 Studer pouches constructed during 1990 and 2011 was performed. Data were analyzed in terms of long-term (>10 years) outcomes. Complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
1
12
1
1
Order By: Relevance
“…Once the posterior plate is created robotically, it is rotated anticlockwise by 908 before urethra-neobladder anastomosis, followed by double cross-folding and true globularization of the neobladder. Our globular robotic iONBs achieved a mean cystometric volume of 514 cm 3 (range 339-1001), which is consistent with mean volumes reported for open ONB series of 430-600 and 450-524 cm 3 for Hautmann [24,25] and Studer [26][27][28] configurations, respectively. Furthermore, the ability to achieve high volumes at low pressure (high compliance) of the robotic iONB lends support to a lowpressure reservoir.…”
Section: Discussionsupporting
confidence: 88%
“…Once the posterior plate is created robotically, it is rotated anticlockwise by 908 before urethra-neobladder anastomosis, followed by double cross-folding and true globularization of the neobladder. Our globular robotic iONBs achieved a mean cystometric volume of 514 cm 3 (range 339-1001), which is consistent with mean volumes reported for open ONB series of 430-600 and 450-524 cm 3 for Hautmann [24,25] and Studer [26][27][28] configurations, respectively. Furthermore, the ability to achieve high volumes at low pressure (high compliance) of the robotic iONB lends support to a lowpressure reservoir.…”
Section: Discussionsupporting
confidence: 88%
“…Several types of neobladder have been described, but all should have the following features: high capacity, low pressure, absence of reflux, and complete voiding by abdominal straining and perineal relaxation (19). In our study, the neobladder capacity was about 375 mL, which was smaller than mean volumes reported for open neobladder construction of 450-524 cm3 (20,21). However, no patient has hydronephrosis or ureterectasis one year after operation.…”
Section: Discussioncontrasting
confidence: 81%
“…Although most studies used SCr measurements, IVU , and CT for laboratory and morphological assessment of RFn, none provided absolute figures in the results section. Neuzillet et al.…”
Section: Studies Describing Rfn As a Secondary Outcomementioning
confidence: 99%